Über einige geographisch-touristische Merkmale und ihre Typologisierung an Beispielen aus den Alpen - Birkenhauer, Josef (ERDKUNDE, 1976)
Concern with the Alps, at first from a specifically regional interest, soon leads to the realization of the well known and great importance of tourism for the physiognomy and economy of the Alps as the so-called fourth (quaternary) grade of historical-social valuation. Fifty examples in the area between Grenoble in the west and the Semmering in the east have been investigated. At the outset the so-called geoformale of the tourist settlement lay-outs were established: low and high nodes, rivieras (aquatic ribbon developments), low and high lanes, montane ribbon developments (sun balconies) - cf. Fig.1. The problem of the urbanisation of the form is approached, as well as it criteria (extent, bazaar- and sauntering-streets, services). Then follows a special investigation of the structure of services. Service units are collated in groups and the number of units in the groups is related to the number of overnight stays with respect to the best season. This results in characteristic threshold values (Fig. 2). These permit the establishment of different size-grades of tourist places (paragraph V). In connection with this a generalizing matrix of tourist places in the Alps is devised (paragraph VI, figure 3) with regard to certain features (size, temporal development, geoformals, altitude, climate). An interpretation of the matrix focuses on the essential correlation of factors (paragraph VI, 3). The results appear to be suited to planning, prognosis, determination of the contribution of the working population for the economic power of the various types. Parallel cases in the German Mittelgebirge (e.g. Black Forest) are briefly referred to.